A model of abusive supervision, self-efficacy, and work engagement among Chinese registered nurses: The mediating role of self-efficacy - Sun, Ning; Zheng, Qiulan; Li, Laiyou; Zhu, Haibo; Liu, Xiufen; Zhou, Shuping; Han, Huihui (Frontiers in Psychology, 2022)
Abusive supervision could negatively influence individual work attitudes, behaviors and work outcomes. Self-efficacy and work engagement can help to increase nursing performance. But few studies have attempted to determine the specific mechanism between them in China. The objective is to analyze the levels of abusive supervision, self-efficacy and work engagement and to explore the relationship between these three variables among Chinese clinical registered nurses. A predictive, cross-sectional quantitative survey was performed in a convenience sample of 923 Chinese clinical nurses. The instruments included the Demographic Data Questionnaire, Abusive Supervision Scale, Self-efficacy Scale and Work Engagement Scale. A total of 702 valid questionnaires were returned, yielding a favorable response rate of 76.1%. The level of abusive supervision was at the mid-low level, with a mean of 1.55. The nurses presented a relative high level of self-efficacy (M=4.97) and work engagement (M=5.01). A statistically significant negative correlation between abusive supervision and self-efficacy (r=-0.21, P<0.01). A statistically significant negative correlation between abusive supervision and work engagement (r=-0.32, P<0.01), and a statistically significant positive correlation between self-efficacy and work engagement (r=0.43, P<0.01). Abusive supervision had a directly negative effect on self-efficacy (β=-0.23, p<0.01) and work engagement (β=-0.24, p<0.01). Self-efficacy positively predicted work engagement (β=0.41, p<0.01). The results indicated that abusive supervision could negatively predict nurses’ work engagement directly and that abusive supervision could also indirectly influence work engagement partly through the mediation of self-efficacy. Nursing managers should take effective measures to prevent and control the abusive management and leadership behavior of head nurses, and improve nurses' self-efficacy, so that nurses can experience full respect, support, and self-confidence. They can devote themselves to work with the greatest enthusiasm.